Do Analyst Earnings Beta Explain Growth Anomaly? - DOAN, Sophie Phuong Thanh (Institutional Knowledge at Singapore Management University, 2010)
Using a measure of cashflow risk derived from analyst forecasts, I find that cashflow risk offers a partial explanation for the value – growth anomaly. In particular, the lowest asset growth portfolio has a higher earnings beta than the highest asset growth portfolio. Approximately cashflow risk measured by earnings beta carries a significant positive risk premium of 1.24% with a t-value of 3.51.